ANALISIS PERAN DAN FUNGSI PERS SEBELUM DAN SESUDAH REFORMASI POLITIK DI INDONESIA - Martini, Rina (JURNAL ILMU SOSIAL, 2014)
The press is often referred to as the fourth pillar of democracy after the executive, legislative, and judicial branches. Press in Indonesia have ups and downs in the roles and functions in respect of some period or era he went through. Prior research found that Era before the Reformation Er , the press in Indonesia fettered by laws and regulation, such as press license , which is a threat to the existence of a publishing company, which at times can be banned publishing business; idealism press shackled to the interests of the state; professional organizations only PWI , as well as the position of the press against the state is weak , the press is acting as agent only government propaganda. Meanwhile, after the Reformation Er , the press in Indonesia experienced its heyday because of laws and regulations in favor of the press; idealism of the free press, as well as professional organizations whose number is infinite, and the position of the state is Strong press , because the press can be a producer for the decision - political decisions. Thus in the Era Before the Reformation , the role and function of the press is limited, fettered, and threatened. After the Reformation Era while the role and function of the press can be realized significantly due to a very large gain freedom.